2010
DOI: 10.3168/jds.2009-2749
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biochemical study of industrially produced San Simón da Costa smoked semi-hard cow's milk cheeses: Effects of storage under vacuum and different modified atmospheres

Abstract: Two batches of smoked, semi-hard (ripened for 45 d) San Simón da Costa cow's milk cheeses with Protected Designation of Origin were used to investigate the chemical, biochemical, and sensorial parameters that may be affected by modified-atmosphere packaging. Cheeses were packaged for 45 d as follows: vacuum packaging, packaging in 100% N(2), packaging in a gas mixture of 20% CO(2)/80% N(2), and packaging in a gas mixture of 50% CO(2)/50% N(2). The San Simón da Costa cheeses were characterized by high contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…Some studies have been carried out to investigate the effect of MAP on the shelf-life and quality of different types of cheeses (e.g., Eliot, Vuillemard, & Edmond, 1998;Esmer, Balkir, Seckin, & Irkin, 2009;González-Fandos, Sanz, & Olarte, 2000;Hotchkiss et al, 2006;Juric, Bertelsen, Mortensen, & Petersen, 2003;Kristensen, Orlien, Mortensen, Brockhoff, & Skibsted, 2000;Robertson, 1993), and MAP is accepted worldwide for use with cheeses. Nevertheless, it has been reported that the use of MAP for dairy products with high percentages of CO 2 may have a detrimental effect on the sensory properties, especially with regard to flavour (Juric et al, 2003;Romani, Sacchetti, Pittia, Pinnavaia, & Dalla Rosa, 2002;Trobetas, Badeka, & Kontominas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been carried out to investigate the effect of MAP on the shelf-life and quality of different types of cheeses (e.g., Eliot, Vuillemard, & Edmond, 1998;Esmer, Balkir, Seckin, & Irkin, 2009;González-Fandos, Sanz, & Olarte, 2000;Hotchkiss et al, 2006;Juric, Bertelsen, Mortensen, & Petersen, 2003;Kristensen, Orlien, Mortensen, Brockhoff, & Skibsted, 2000;Robertson, 1993), and MAP is accepted worldwide for use with cheeses. Nevertheless, it has been reported that the use of MAP for dairy products with high percentages of CO 2 may have a detrimental effect on the sensory properties, especially with regard to flavour (Juric et al, 2003;Romani, Sacchetti, Pittia, Pinnavaia, & Dalla Rosa, 2002;Trobetas, Badeka, & Kontominas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Garabal et al (2010) showed that vacuum packaging is the best method for retaining the sensory quality of San Simón da Costa smoked semi-hard cheeses.…”
Section: Odor and Tastementioning
confidence: 99%
“…Increase in pH values was also reported in a study conducted by Maniar et al (1994) on direct-set Cottage cheese stored at 4°C and was justified as the absorption of the produced acid by the curd from the cream. Garabal et al (2010) associated their observation, about the pH increase, in industrially made smoked semi-hard cheese (San Simón da Costa, from cow's milk), which increased from 5.25 in ripened cheese to 5.45, 5.46, and 5.40 for gas mixtures of 100% N 2 ,2 0 %C O 2 /80% N 2 , and 50% CO 2 /50% N 2 , respectively, after 45 days of storage, to proteolysis and associated formation of amines and ammonium. Temiz (2010) observed an increase in the pH values of sliced Kashar cheese, which was followed by a subsequent depression as the lowest final pH value (5.70) was determined in cheese under 100% CO 2 .…”
Section: Ph Changesmentioning
confidence: 99%
See 2 more Smart Citations